Food policy reforms in Central Asia: setting the research priorities - Babu, Suresh Chandra; Tashmatov, Alisher (International Food Policy Research Institute, 2000)
Since the break-up of the Soviet Union, the countries of the Central Asia region have undertaken varying levels of policy reforms in their food, agricultural, and natural resources sectors. Despite these reforms, available evidence indicates that poverty and natural resource degradation are on the rise in this region...This volume brings together a group of policy researchers from Central Asia and elsewhere to address the emerging food policy issues, to identify the information gaps,and to set priorities for policy research. 'Food Policy Reforms in Central Asia : Setting the Research Priorities' is an outcome of the initial collaboration between the International Food Policy Research Institute (IFPRI) and the institutions involved in analyzing and advising policymakers on food policy reforms in the Central Asia region'...The papers of this volume identify key issues that need immediate research attention from those involved in the food policy reform process in the region."" (Excerpted from Forward by Per Pinstrup-Andersen and Abduvokhid Juraev)